2010
DOI: 10.1001/archinternmed.2010.391
|View full text |Cite|
|
Sign up to set email alerts
|

The Comparative Safety of Analgesics in Older Adults With Arthritis

Abstract: The comparative safety of analgesics varies depending on the safety event studied. Opioid use exhibits an increased relative risk of many safety events compared with nsNSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
296
2
13

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 368 publications
(319 citation statements)
references
References 28 publications
8
296
2
13
Order By: Relevance
“…While HIV-infected patients frequently experience pain and are in need of effective treatment, 13,17,46 data suggest there may be potential harm from opioids. For example, data indicate that compared to other analgesics, opioids are associated with increased cardiovascular events and fractures 19,21 both of which occur more commonly among HIV-infected patients. 26,47 Similarly, some evidence suggests that opioids may adversely impact the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While HIV-infected patients frequently experience pain and are in need of effective treatment, 13,17,46 data suggest there may be potential harm from opioids. For example, data indicate that compared to other analgesics, opioids are associated with increased cardiovascular events and fractures 19,21 both of which occur more commonly among HIV-infected patients. 26,47 Similarly, some evidence suggests that opioids may adversely impact the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The benefits of opioids for treating painful conditions, such as neuropathy and osteonecrosis, which may occur more commonly among HIV-infected patients, must be balanced against 16,17 the possibility of increased risk for harm. Opioids may impact immune function, 18 be associated with toxicities [19][20][21] and interact with antiretrovirals. 22 There are limited recent data examining factors associated with opioid prescribing to HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Other harms, especially falls and fractures, may be more common and worrisome among older adults. 5 Falls are an important mechanism of serious trauma and the most common cause of injury-related emergency visits among older adults. 6,7 Fracture is a serious potential consequence of falling, which among older adults can lead to significant morbidity, loss of independence, or death, especially in the case of hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Fracture is a serious potential consequence of falling, which among older adults can lead to significant morbidity, loss of independence, or death, especially in the case of hip fracture. 8,9 Most prior studies have found positive associations between the use of opioid analgesics and fractures in older adults, 5,[10][11][12] but evidence for an association between opioid use and falls has been inconsistent. 13,14 Importantly, chronic musculoskeletal pain is also associated with declines in physical function [14][15][16][17][18] and increased risk of falling.…”
Section: Introductionmentioning
confidence: 99%
“…8,34,[41][42][43][44] As a result, a recent clinical review recommends initiating long-term opioid therapy only when patients have moderate to severe pain leading to substantial impairment in daily living and when all other treatment modalities have failed. 45 This is not a recommendation founded on demonstrable evidence of benefits exceeding harms.…”
Section: Harms Of Therapymentioning
confidence: 99%